Intracellular postsynaptic cannabinoid receptors link thyrotropin-releasing hormone receptors to TRPC-like channels in thalamic paraventricular nucleus neurons. (17th December 2015) - Zhang, L.; Kolaj, M.; Renaud, L.P.
Graphical abstract: Highlights: TRH receptors engage novel signaling pathways in PVT neurons. TRH-induced current is mediated via activation of phosphatidylcholine-specific PLC. Postsynaptic intracellular CB1 and CB2 receptors suppress TRPC-like channel opening. TRH enhancement of LTS requires cannabinoid receptor activation. TRH-induced responses lack evidence for involvement of presynaptic CB receptors. Abstract: In rat thalamic paraventricular nucleus of thalamus (PVT) neurons, activation of thyrotropin-releasing hormone (TRH) receptors enhances excitability via concurrent decrease in G protein-coupled inwardly-rectifying potassium (GIRK)-like and activation of transient receptor potential cation (TRPC)4/5-like cationic conductances. An exploration of intracellular signaling pathways revealed the TRH-induced current to be insensitive to phosphatidylinositol-specific phospholipase C (PI-PLC) inhibitors, but reduced by D609, an inhibitor of phosphatidylcholine-specific PLC (PC-PLC). A corresponding change in the I – V relationship implied suppression of the cationic component of the TRH-induced current. Diacylglycerol (DAG) is a product of the hydrolysis of PC. Studies focused on the isolated cationic component of the TRH-induced response revealed a reduction by RHC80267, an inhibitor of DAG lipase, the enzyme involved in the hydrolysis of DAG to the endocannabinoid 2-arachidonoylglycerol (2-AG). Further investigation revealed enhancement of the cationic component in the presence of either JZL184 or WWL70, inhibitors of enzymes involved in the hydrolysis of 2-AG. A decrease in the TRH-induced response was noted in the presence of rimonabant or SR144528, membrane permeable CB1 and CB2 receptor antagonists, respectively. A decrease in the TRH-induced current by intracellular, but not by bath application of the membrane impermeable peptide hemopressin, selective for CB1 receptors, suggests a postsynaptic intracellular localization of these receptors. The TRH-induced current was increased in the presence of arachidonyl-2′-chloroethylamide (ACEA) or JWH133, CB1 and CB2 receptor agonists, respectively. The PI3-kinase inhibitor LY294002, known to inhibit TRPC translocation, decreased the response to TRH. In addition, a TRH-induced enhancement of the low-threshold spike was prevented by both rimonabant, and SR144528. TRH had no influence on excitatory or inhibitory miniature postsynaptic currents, suggesting presynaptic CB receptors are not involved in this situation. Collectively, the data imply that activation of TRH receptors in these midline thalamic neurons engages novel signaling pathways that include postsynaptic intracellular CB1 and CB2 receptors in the activation of TRPC4/5-like channels.